Penerapan Metode Brainstorming dalam Meningkatkan Motivasi Belajar Aqidah Akhlak Siswa Kelas XI A MA Plus Sunan Kalijaga, Pogalan, Trenggalek, Pada Semester Genap Tahun Ajaran 2023-2024 - Ida Pujirahayu; Mochammad Rizal Fanani; Uswatun Hasanah (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2025)
This article is about the importance of learning motivation, which serves as an effort to achieve achievement. In teaching and learning, motivation is a very important factor because it can foster students' interest in learning. Students with strong motivation will have the energy to carry out learning activities. The lack of learning motivation in Aqidah Akhlak lessons at MA PLUS SUNAN KALIJAGA class XI A has resulted in unsatisfactory learning outcomes, falling below the Minimum Completion Criteria (KKM). Thus, students' learning outcomes are less successful because the average score is lower than the KKM, due to the use of conventional methods. Therefore, a learning method that can make students learn with enthusiasm and more meaning is needed, namely the brainstorming learning method. The purpose of this study is to determine the effectiveness of applying the brainstorming method to improve students' learning motivation. The author applies classroom action research with the model from Kemis and McTaggart, which consists of four components: planning, acting, observing, and reflecting. This study shows that the application of the brainstorming method can improve students' learning motivation.